E-readiness Assessment of National Agricultural Research in India (Indian Journal of Extension Education, 2023)
The digital era has ushered in profound transformations across global industries, where the integration of information and communication technologies (ICTs) is crucial for growth, productivity, and sustainability. Agriculture, in particular, relies on this digital imperative to enhance food security, sustainability, and economic development. The National Agricultural Research System (NARS) plays a pivotal role in shaping the nation’s agricultural progress addressing food security, productivity, climate change, and farmer livelihoods, the NARS must embrace digital advancements. The study was conducted at NARS of India, 660 scientists were selected from 102 ICAR institutes using multistage stratified random sampling techniques. E-readiness was measured based on a conceptual framework developed by Tugrul & Maru (2003) and the STOPE framework. The framework measures the dimensions like strategy, technology, organizational support, HR support, and e-culture. The result provides a comprehensive understanding of NARS’s preparedness for digital transformation. While there are clear strengths in strategy, technology, and human resources support, areas requiring improvement, particularly organizational support and aspects of e-culture readiness, should be addressed with strategic initiatives.